Fitokimia Daun Kemangi (Ocimum x citriodorum L.) dan Pengaruhnya Sebagai Water Additive Terhadap Kecernaan Nutrien Pakan Ayam Broiler - Jet Saartje Mandey; Cherly Joula Pontoh (Jurnal Ilmu Peternakan Terapan, 2020)
The study was conducted to analyze the phytochemicals of basil leaves (Ocimum x citriodorum L.)and to evaluate the effect of basil leaves juice as an additive on nutrient digestibility of broilerchicken diet. This study used 20 male broilers (35 days old). The research parameters werephytochemical, proximate, and digestibility analysis. The data of basil leaves phytochemical andproximate analysis were analyzed using descriptive analysis. The digestibility were analyzed usinga Completely Randomized Design (CRD) by 4 treatments and 5 replications. The research wasconducted for 10 days consisting of 7 days for maintenance period and 3 days for total collectionperiod. The digestibility treatments consisted of 0 mL, 10 mL, 20 mL, and 30 mL basil leaves juice/Ldrinking water. The results showed that giving basil leaves juice had a good effect on nutrientdigestibility of broiler chickens and could be used up to 20 mL/L in drinking water.